Spatial transcriptomic characteristics of gastric cancer in young and the expression and role of TMEM176B in gastric cancer cells - Zhenhua Jiang; Yongfeng Wang; Chi Zhang; Shuangyin Han (European Journal of Medical Research)
Abstract Background Gastric cancer in young (GCY) is increasing in incidence with poor prognosis. Current screening and molecular methods are inadequate, necessitating new approaches to explore its pathogenesis. This study used spatial transcriptomic sequencing (ST-seq) to analyze the cellular composition of gastric cancer (GC) tumors, compare gene expression patterns, explore signaling pathways, and investigate the role of the differentially expressed gene (DEG) TMEM176B in GCY. Methods The surgical specimens of six patients with GCY were included to construct a tissue microarray containing the tumor core region (TCR), cancer-adjacent tissue (CAT), and normal gastric tissue (NGT). ST-seq was performed to obtain the transcript expression levels at different spatial locations. After quality control, normalization, standardization, clustering, dimensionality reduction, and cell-type prediction analyses were carried out to identify the DEGs. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were used to clarify the underlying mechanisms of GC. Based on the results, TMEM176B was selected for functional analysis. Western blotting was used to assess TMEM176B expression in normal gastric cells and cancerous cells. shRNA-mediated TMEM176B knockdown in cancer cells was used for phenotypic analysis, proliferation assays, and apoptosis experiments. Results This study identified heterogeneous cell populations in GCY tissues. Exactly 18,082 DEGs were found between the TCR and CAT, mainly enriched in the IL-17, AGE-RAGE, and relaxin pathways. Moreover, 17,586 DEGs were identified between the TCR and NGT, primarily related to the HIF-1 and apoptosis pathways. TMEM176B was a key DEG in the TCR vs. CAT and TCR vs. NGT comparisons. It was highly expressed in GCY tissues and GC cell lines. Further analysis using The Cancer Genome Atlas database confirmed its oncogenic effects. TMEM176B knockdown in GC cell lines inhibited cell proliferation (reduced CCK8 and colony formation), increased apoptosis (higher Bax/Bcl2 ratio), and arrested the cell cycle in the G0/G1 phase. Conclusions This study used ST-seq to map the transcriptomic profiles of the TCR, CAT, and NGT in patients with GCY, investigating gene spatial expression patterns and tumor heterogeneity. We identified TMEM176B’s role in GC development and progression, offering molecular targets and a foundation for future treatments.